2019
DOI: 10.1186/s12879-019-4013-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B surface antigen (HBsAg) positivity and its associated factors in Rwanda

Abstract: Background The epidemiology of hepatitis B virus (HBV) infection in the general population in Rwanda is not well known. This study examined the prevalence of HBV surface antigen (HBsAg) positivity and associated risk factors among people aged 25 years and over in an organized national screening campaign. Methods This is a cross-sectional study using data from a nationwide HBV screening campaign organized by the Rwanda Biomedical Centre from March to October 2018. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 24 publications
9
45
0
Order By: Relevance
“…Higher odds for HBV were associated with higher frequencies of sexual encounters and, perhaps, more exposure to casual sex workers through mobile employment. These findings are similar to other studies done in Rwanda 18 21 29 and in Burkina Faso. 30 Contrary to HIV and HBV, HCV infection was more common in rural areas, and this is consistent with previous findings from Rwanda and other African countries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Higher odds for HBV were associated with higher frequencies of sexual encounters and, perhaps, more exposure to casual sex workers through mobile employment. These findings are similar to other studies done in Rwanda 18 21 29 and in Burkina Faso. 30 Contrary to HIV and HBV, HCV infection was more common in rural areas, and this is consistent with previous findings from Rwanda and other African countries.…”
Section: Discussionsupporting
confidence: 93%
“… 12 16 In 2015, Rwanda DHS showed that the prevalence of HIV in the general population was 3%, with a higher prevalence in urban than rural areas (6% vs 2.4%, respectively). 17 Recent studies on HBV in Rwanda revealed that the prevalence of hepatitis B surface antigen (HBsAg) among people screened was 3.9%, 18 19 while the prevalence of anti-HCV was between 6.2% and 6.6% with viremia of 52%. 20 21 In 2017, a study conducted among PLHIV found that the prevalence of co-infections with HBV and HCV were 4.2% and 4.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this systematic review and meta-analysis also revealed that pregnant women who had a tattoo on their body were infected with HBV more likely than those who had not, similarly with the studies done in Ethiopia [36,41], Sudan [68], Turkey [51], Ghana [51], Nigeria [59], and Rwanda [69]. It might be due to a gap in the cleaning and sterilizing of materials for the procedure.…”
Section: Discussionsupporting
confidence: 76%
“…A similar association of male sex with HBV infection was also found in different studies from Pakistan, Rwanda, South Africa. [15][16][17] But in our study, the number of male participants was much lower which needs special attention in future programming to focus on males to participate voluntarily in such a study.…”
Section: Discussionmentioning
confidence: 62%